Potensi dan Kendala dalam Pengembangan Pantai Kelating sebagai Daya Tarik Wisata di Desa Kelating Kabupaten Tabanan - Silalahi, Nina Herlina Br; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p20, 2018)
This study is about the potentials and constraints in developing of Kelating Beach as a tourist attraction at Village of Kelating, Tabanan Regency. This study is motivated by there’s no serious management for Kelating Beach, although this beach has the great potential to developed. This study is important to know potentials and constraints in developing of Kelating Beach as a tourist attraction at Village of Kelating, Tabanan Regency. This study using a qualitative approach by data collected by observation,interview, and documentation.  Data used in this study is qualitative and quantitative and the data used in this study is derived from the primary and secondary data. Mechanical determination informants using purposive sampling. Analysis of the data used in this study is descriptive qualitative method of analysis. Based on the results of this study, Kelating Beach has great potentials to developed  to be a tourist attraction at Village of Kelating. Physical Potentials of Kelating Beach are the beach view of still natural with black sand, surrounded by hills and crag, there’s  a bat cave, mini waterfall, there’s a temple located in front of the beach the named is Taman AgungTemple. In addition, local communities with art and culture, daily activities or communities attitude of friendly also add value a tourist attraction at Village of Kelating, Tabanan Regency. Constraints in developing of Kelating Beach potentials from aspect: tourism community development, tourism product development and marketing of integrated. But in developing Kelating Beach as a tourist attraction at Village of Kelating, Tabanan Regency has constraints one of which is not yet active tourism management agency optimally . Keywords : Potential and Constrain, Developing the Tourist Attraction.